Nomenclatural and botanical history of the Cuban endemic palm Coccothrinax crinita (R.D.Hoyt) Becc. - Kanchi Gandhi; Javier Francisco-Ortega; Larry Noblick; Selvyn Valenzuela; Julio Martínez Betancourt; Rosalina Montes Espín; M. Patrick Griffith (Kew Bulletin, 2026)

Association between anticholinergic and sedative medications and physical functioning: data from the Canadian longitudinal study on aging (CLSA) - Keren Pelen; Patrick Boissy; Karina Lebel; Alexandra Mayhew; Marla K Beauchamp; Lauren E Griffith; Megan E O’Connell; Sarah N Hilmer; Marie-Laure Baroud; Caroline Sirois; Frank Moriarty; Jean-Philippe Turcotte; et al. (European Journal of Clinical Pharmacology, 2026)

Spatial extent and age-related bioaccumulation of fluoride in the bones of house sparrows around aluminium smelting operations - Max M. Gillings; Riccardo Ton; Phoebe Lewis; Minna Saaristo; Mark Patrick Taylor; Simon C. Griffith (Environmental Research, 2025)

Telomere length declines with mean blood lead concentration in an urban passerine - Heung Ying Janet Chik; Max M. Gillings; Riccardo Ton; Marco van der Velde; Mark Patrick Taylor; John P. Swaddle; Hannah L. Dugdale; Simon C. Griffith (Environmental Research, 2025)

Exposure to lead (Pb) contamination heightens predator avoidance behaviours in an urban bird - Heung Ying Janet Chik; Joseph F. Di Liberto; Max M. Gillings; Riccardo Ton; Mark Patrick Taylor; John P. Swaddle; Simon C. Griffith (Animal Behaviour, 2025)

Blood lead increases and haemoglobin decreases in urban birds along a soil contamination gradient in a mining city - Max M. Gillings; Riccardo Ton; Tiarne Harris; Mark Patrick Taylor; Simon C. Griffith (Environmental Research, 2024)

Genomic patterns of native palms from the Leeward Antilles confirm single-island endemism and guide conservation priorities - James A. R. Clugston; Quirijn Coolen; Erik Houtepen; André S. J. van Proosdij; Ayress D. Grinage; M. Patrick Griffith (Conservation Genetics, 2024)
Systematic study of the palm (Arecaceae) flora from the Leeward Antilles marked both Sabal antillensis and Sabal lougheediana as endemic to Curaçao and Bonaire respectively. Although both species are emergent, obvious and charismatic elements of the Antillean flora, they were only described within the last decade. Sabal lougheediana is in demographic crisis as a result of constant ungulate pressure prohibiting seedling establishment, while S. antillensis is thriving as a result of careful management. Given the surprisingly recent discovery of these two species, and the severity of the conservation concern, genomic data can help inform whether these taxa are in fact well-circumscribed species, and help to guide further conservation actions. To investigate genomic diversity, we employed RADSeq data from samples throughout the range of both species. Results show significant genetic distance and fixation between the two taxa as currently circumscribed, as well as reduced genetic diversity and increased inbreeding in both species. Multivariate analysis of genetic distance and Bayesian clustering analysis both show clear and significant separation of the two taxa. Parallel assay of ex situ collections informs how future development of germplasm reserves can help support conservation of both species. We provide recommendations to help conserve these two unique and distinct species.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Current management practices do not adequately safeguard endangered plant species in conservation collections - Zoe Diaz-Martin; Jeremie Fant; Kayri Havens; William Cinea; Joanna M. Tucker Lima; M. Patrick Griffith (Biological Conservation, 2023)

Response of Stream Metabolism to Coarse Woody Debris Additions Along a Catchment Disturbance Gradient - Brian J. Roberts; Natalie A. Griffiths; Jeffrey N. Houser; Patrick J. Mulholland (Ecosystems, 2022)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Applying the zoo model to conservation of threatened exceptional plant species - Jordan Wood; Jonathan D. Ballou; Taylor Callicrate; Jeremie B. Fant; M. Patrick Griffith; Andrea T. Kramer; Robert C. Lacy; Abby Meyer; Sara Sullivan; Kathy Traylor‐Holzer; Seana K. Walsh; Kayri Havens (Conservation Biology, 2020)
Maintaining a living plant collection is the most common method of ex situ conservation for plant species that cannot be seed banked (i.e., exceptional species). Viability of living collections, and their value for future conservation efforts, can be limited without coordinated efforts to track and manage individuals across institutions. Using a pedigree‐focused approach, the zoological community has established an inter‐institutional infrastructure to support long‐term viability of captive animal populations. We assessed the ability of this coordinated metacollection infrastructure to support the conservation of 4 plant species curated in living collections at multiple botanic gardens around the world. Limitations in current practices include the inability to compile, share, and analyze plant collections data at the individual level, as well as difficulty in tracking original provenance of ex situ material. The coordinated metacollection framework used by zoos can be adopted by the botanical community to improve conservation outcomes by minimizing the loss of genetic diversity in collections. We suggest actions to improve ex situ conservation of exceptional plant species, including developing a central database to aggregate data and track unique individuals of priority threatened species among institutions and adapting a pedigree‐based population management tool that incorporates life‐history aspects unique to plants. If approached collaboratively across regional, national, and global scales, these actions could transform ex situ conservation of threatened plant species.

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Complex reproductive secretions occur in all extant gymnosperm lineages: a proteomic survey of gymnosperm pollination drops - Natalie Prior; Stefan A. Little; Ian Boyes; Patrick Griffith; Chad Husby; Cary Pirone-Davies; Dennis W. Stevenson; P. Barry Tomlinson; Patrick von Aderkas (Plant Reproduction, 2019)

Will the same ex situ protocols give similar results for closely related species? - M. Patrick Griffith; Michael Calonje; Alan W. Meerow; Javier Francisco-Ortega; Lindy Knowles; Rudy Aguilar; Freddy Tut; Vanessa Sánchez; Abby Meyer; Larry R. Noblick; Tracy M. Magellan (Biodiversity and Conservation, 2017)

The effect of protected areas on forest disturbance in the Carpathian Mountains 1985–2010 - Van Butsic; Catalina Munteanu; Patrick Griffiths; Jan Knorn; Volker C. Radeloff; Juraj Lieskovský; Daniel Mueller; Tobias Kuemmerle (Conservation Biology, 2017)
Protected areas are a cornerstone for forest protection, but they are not always effective during times of socioeconomic and institutional crises. The Carpathian Mountains in Eastern Europe are an ecologically outstanding region, with widespread seminatural and old‐growth forest. Since 1990, Carpathian countries (Czech Republic, Hungary, Poland, Romania, Slovakia, and Ukraine) have experienced economic hardship and institutional changes, including the breakdown of socialism, European Union accession, and a rapid expansion of protected areas. The question is how protected‐area effectiveness has varied during these times across the Carpathians given these changes. We analyzed a satellite‐based data set of forest disturbance (i.e., forest loss due to harvesting or natural disturbances) from 1985 to 2010 and used matching statistics and a fixed‐effects estimator to quantify the effect of protection on forest disturbance. Protected areas in the Czech Republic, Slovakia, and the Ukraine had significantly less deforestation inside protected areas than outside in some periods; the likelihood of disturbance was reduced by 1–5%. The effectiveness of protection increased over time in these countries, whereas the opposite was true in Romania. Older protected areas were most effective in Romania and Hungary, but newer protected areas were more effective in Czech Republic, and Poland. Strict protection (International Union for Conservation of Nature [IUCN] protection category Ia‐II) was not more effective than landscape‐level protection (IUCN III‐VI). We suggest that the strength of institutions, the differences in forest privatization, forest management, prior distribution of protected areas, and when countries joined the European Union may provide explanations for the strikingly heterogeneous effectiveness patterns among countries. Our results highlight how different the effects of protected areas can be at broad scales, indicating that the effectiveness of protected areas is transitory over time and space and suggesting that generalizations about the effectiveness of protected areas can be misleading.

Carbon emissions from agricultural expansion and intensification in the Chaco - Matthias Baumann; Ignacio Gasparri; María Piquer‐Rodríguez; Gregorio Gavier Pizarro; Patrick Griffiths; Patrick Hostert; Tobias Kuemmerle (Global Change Biology, 2017)
Carbon emissions from land‐use changes in tropical dry forest systems are poorly understood, although they are likely globally significant. The South American Chaco has recently emerged as a hot spot of agricultural expansion and intensification, as cattle ranching and soybean cultivation expand into forests, and as soybean cultivation replaces grazing lands. Still, our knowledge of the rates and spatial patterns of these land‐use changes and how they affected carbon emissions remains partial. We used the Landsat satellite image archive to reconstruct land‐use change over the past 30 years and applied a carbon bookkeeping model to quantify how these changes affected carbon budgets. Between 1985 and 2013, more than 142 000 km 2 of the Chaco's forests, equaling 20% of all forest, was replaced by croplands (38.9%) or grazing lands (61.1%). Of those grazing lands that existed in 1985, about 40% were subsequently converted to cropland. These land‐use changes resulted in substantial carbon emissions, totaling 824 Tg C between 1985 and 2013, and 46.2 Tg C for 2013 alone. The majority of these emissions came from forest‐to‐grazing‐land conversions (68%), but post‐deforestation land‐use change triggered an additional 52.6 Tg C. Although tropical dry forests are less carbon‐dense than moist tropical forests, carbon emissions from land‐use change in the Chaco were similar in magnitude to those from other major tropical deforestation frontiers. Our study thus highlights the urgent need for an improved monitoring of the often overlooked tropical dry forests and savannas, and more broadly speaking the value of the Landsat image archive for quantifying carbon fluxes from land change.

Population‐level consequences for wild fish exposed to sublethal concentrations of chemicals – a critical review - Patrick B Hamilton; Ian G Cowx; Marjorie F Oleksiak; Andrew M Griffiths; Mats Grahn; Jamie R Stevens; Gary R Carvalho; Elizabeth Nicol; Charles R Tyler (Fish and Fisheries, 2016)
Concentrated chemical spills have been shown to impact adversely on fish populations and even cause localized population extinctions. Evaluating population‐level impacts of sublethal exposure concentrations is, however, complex and confounded by other environmental pressures. Applying effect measures derived from laboratory‐based chemical exposures to impacts in wild fish populations is constrained by uncertainty on how biochemical response measures (biomarkers) translate into health outcomes, lack of available data for chronic exposures and the many uncertainties in available fish population models. Furthermore, wild fish show phenotypic plasticity and local adaptations can occur that adds geographic and temporal variance on responses. Such population‐level factors are rarely considered in the chemical risk assessment process and can probably be derived only from studies on wild fish. Molecular technologies, including microsatellite and SNP genotyping, and RNAS eq for gene expression studies, are advancing our understanding of mechanisms of eco‐toxicological response, tolerance, adaptation and selection in wild populations. We examine critically the application of such approaches with examples including using microsatellites that has identified roach ( Rutilus rutilus ) populations living in rivers contaminated with sewage effluents that are self‐sustaining, and studies of stickleback ( Gasterosteus aculeatus ) and killifish ( Fundulus heteroclitus ) that have identified genomic regions under selection putatively related to pollution tolerance. Integrating data on biological effects between laboratory‐based studies and wild populations, and building understanding on adaptive responses to sublethal exposure are some of the priority research areas for more effective evaluation of population risks and resilience to contaminant exposure.

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Molecular Systematics of Threatened Seed Plant Species Endemic in the Caribbean Islands - Nora Oleas; Brett Jestrow; Michael Calonje; Brígido Peguero; Francisco Jiménez; Rosa Rodríguez-Peña; Ramona Oviedo; Eugenio Santiago-Valentín; Alan W. Meerow; Melissa Abdo; Michael Maunder; M. Patrick Griffith; et al. (The Botanical Review, 2013)

What is the Conservation Value of a Plant in a Botanic Garden? Using Indicators to Improve Management of Ex Situ Collections - Angelica Cibrian-Jaramillo; Abby Hird; Nora Oleas; Helen Ma; Alan W. Meerow; Javier Francisco-Ortega; M. Patrick Griffith (The Botanical Review, 2013)

Special Issue on Genetics and Plant Conservation in Latin America - M. Patrick Griffith; Javier Francisco-Ortega; Angelica Cibrian-Jaramillo (The Botanical Review, 2013)

An ocean observation system for monitoring the affects of climate change on the ecology and sustainability of pelagic fisheries in the Pacific Ocean - Simon J. Nicol; Valerie Allain; Graham M. Pilling; Jeff Polovina; Marta Coll; Johann Bell; Paul Dalzell; Peter Sharples; Robert Olson; Shane Griffiths; Jeffrey M. Dambacher; Jock Young; et al. (Climatic Change, 2013)

Structural cladistic study of Cocoseae, subtribe Attaleinae (Arecaceae): Evaluating taxonomic limits in Attaleinae and the neotropical genus Syagrus - Larry R. Noblick; William J. Hahn; M. Patrick Griffith (Brittonia, 2013)

Climate Change Adaptation for the US National Wildlife Refuge System - Brad Griffith; J. Michael Scott; Robert Adamcik; Daniel Ashe; Brian Czech; Robert Fischman; Patrick Gonzalez; Joshua Lawler; A. David McGuire; Anna Pidgorna (Environmental Management, 2009)

Land use change in Southern Romania after the collapse of socialism - Tobias Kuemmerle; Daniel Müller; Patrick Griffiths; Marioara Rusu (Regional Environmental Change, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas - Lisa Patrick; Jessica Cable; Daniel Potts; Danielle Ignace; Greg Barron-Gafford; Alden Griffith; Holly Alpert; Natasja Van Gestel; Traesha Robertson; Travis E. Huxman; John Zak; Michael E. Loik; et al. (Oecologia, 2007)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)